Growth of V2O5 Films for Battery Applications by Pulsed Chemical Vapor Deposition. (19th June 2018) - Kazadojev, Igor I; O'Brien, S; Ryan, Louise P; Modreanu, M; Osiceanu, P; Somacescu, S; Vernardou, D; Pemble, Martyn E; Povey, Ian M
Abstract : Pulsed chemical vapor deposition (CVD), or more correctly atomic layer deposition (ALD) outside of the ALD thermal window, was used to grow vanadium pentoxide films using Tetrakis(dimethylamino)vanadium (IV) (V(NMe2 )4 ) as the vanadium source and either oxygen-argon plasma, oxygen or water as the co-reagent. Growths were performed at 150-300 ° C for 400 cycles, resulting in a range of both stoichiometric and non-stoichiometric vanadium oxides. Post growth annealing in air at 400 ° C for both thermal and plasma assisted methods resulted in the formation of α–V2 O5 . Electrochemical characterization revealed that the samples grown at 250 ° C using a plasma process and a post growth anneal demonstrate the best electrochemical properties in terms of current density and charge density with values of 0.35 mAcm -2 and 55 mCcm -2 respectively. The influence of growth parameters on material properties is discussed.